2020
DOI: 10.1093/gji/ggaa016
|View full text |Cite
|
Sign up to set email alerts
|

Noise-based ballistic wave passive seismic monitoring – Part 2: surface waves

Abstract: SUMMARY We develop a new method to monitor and locate seismic velocity changes in the subsurface using seismic noise interferometry. Contrary to most ambient noise monitoring techniques, we use the ballistic Rayleigh waves computed from 30 d records on a dense nodal array located above the Groningen gas field (the Netherlands), instead of their coda waves. We infer the daily relative phase velocity dispersion changes as a function of frequency and propagation distance with a cross-wavelet transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 70 publications
(85 reference statements)
1
15
0
Order By: Relevance
“…We made use of not only the 36 station pairs within the SPMS subarray, but also of longer offset pairs within a set of 10 additional stations around it (orange triangles in Figure 1), which are approximately (within 0.5 m) on the same topographic plane as the SPMS stations and could therefore be rotated into the same slope-aligned coordinate system. In total, we considered a range of interstation distances from 4.6 to 57.6 m. Cross-correlations with similar interstation distances (binned in 0.25 m increments) were stacked together to help increase signal-to-noise ratio (Boué et al, 2013;Mordret et al, 2014Mordret et al, , 2020Nakata et al, 2015). Cross-correlations were then high-pass filtered at the frequency that would produce a wavelength equal to the interstation distance-typically the limit for FTAN analysis (Luo et al, 2015)-at a velocity of 350 m/s (a value chosen empirically after initial analysis).…”
Section: Group Velocity Measurement and Velocity Modelmentioning
confidence: 99%
“…We made use of not only the 36 station pairs within the SPMS subarray, but also of longer offset pairs within a set of 10 additional stations around it (orange triangles in Figure 1), which are approximately (within 0.5 m) on the same topographic plane as the SPMS stations and could therefore be rotated into the same slope-aligned coordinate system. In total, we considered a range of interstation distances from 4.6 to 57.6 m. Cross-correlations with similar interstation distances (binned in 0.25 m increments) were stacked together to help increase signal-to-noise ratio (Boué et al, 2013;Mordret et al, 2014Mordret et al, , 2020Nakata et al, 2015). Cross-correlations were then high-pass filtered at the frequency that would produce a wavelength equal to the interstation distance-typically the limit for FTAN analysis (Luo et al, 2015)-at a velocity of 350 m/s (a value chosen empirically after initial analysis).…”
Section: Group Velocity Measurement and Velocity Modelmentioning
confidence: 99%
“…Where boreholes are not available, active or passive seismic experiments may help to constrain the shallow velocity structure, and to adequately quantify the magnitude of shallow changes. New methods focusing on correlating specific types of waves may also allow to better locate shallow changes (Mordret et al, 2020).…”
Section: Standardizing Seismological Dv/v To Overcome the Limitations Of Geomorphic Datamentioning
confidence: 99%
“…At a depth of 50 m, used by Fokker and Ruigrok [16], motion of the first overtone dominates over the motion of the fundamental mode. In Mordret et al [19], it is shown that, in the Groningen setting, the first overtone of the Rayleigh wave has a higher sensitivity to velocity changes than the fundamental mode.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a dense surface network of stations was used to detect velocity changes in refracted waves over a one-month period [18]. Using the same dense array of 417 stations, a novel implementation of passive image interferometry was tested [19]. Following heavy rain, they found a velocity reduction that propagates downward with time.…”
Section: Introductionmentioning
confidence: 99%